Tissue specificity drives protective immunity against Staphylococcus aureus infection - Beesetty, Pavani; Si, Youhui; Li, Zhaotao; Yang, Ching; Zhao, Fan; Chong, Anita S.; Montgomery, Christopher P. (Frontiers in Immunology, 2022)
Infections caused by Staphylococcus aureus range from mild to severe and frequently recur. Emerging evidence suggests that the site and severity of infection drive the potency of elicited immune responses and susceptibility to recurrent infection. In this study, we used tractable mouse models of S. aureus skin infection (SSTI) and pneumonia to determine the relative magnitude of elicited protective immunity. Surprisingly, despite both SSTI and pneumonia eliciting antibody and local effector T cell responses, only SSTI elicited protective antibody and memory T cell responses and subsequent protection against secondary SSTI and pneumonia. The failure of pneumonia to elicit protective immunity was attributed to an inability of S. aureus pneumonia to elicit toxin-specific antibodies that confer protection during secondary infection and was associated with a failure to expand antigen-specific memory T cells. Taken together, these findings emphasize the importance of understanding protective immunity in the context of the tissue-specificity.